Rectus femoris cross sectional area and timed up and go test potential useful of as a predictor of sarcopenia and mortality in idiopathic pulmonary fibrosis - Fernández-Jiménez, Rocío; Cabrera-Cesar, Eva; Sanmartín-Sánchez, Alicia; Sánchez-Garcia, Ana; Espildora-Hernandez, Francisco; Vegas-Aguilar, Isabel; del Mar Amaya-Campos, Maria; Guirado-Pelaez, Patricia; Simón-Frapolli, Victor; Murri, Mora; Garrido-Sánchez, Lourdes; Piñel-Jimenez, Lorena; et al. (Frontiers in Nutrition, 2024)
Introduction Idiopathic pulmonary fibrosis (IPF) is a progressive lung disease often complicated by sarcopenia, significantly impacting patient outcomes. This study investigates the prevalence and clinical implications of sarcopenia in IPF patients using morphofunctional assessment methods. Materials and methods Eighty-four IPF patients (predominantly male) were evaluated for sarcopenia using the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criteria. Assessments included bioelectrical impedance vectorial analysis (Nutrilab, Akern), handgrip strength (HGS), Timed Up and Go test (TUG), and nutritional ultrasound (NU) measurements of rectus femoris and abdominal adipose tissue. Statistical analysis was performed (version 2.3.28 for macOS) to obtain sarcopenia cut-off points for the different techniques, and then the predictive capacity of these values for survival was analyzed using a Kaplan–Meier curve. Results Sarcopenia was prevalent in 20.2% of the cohort. Sarcopenic patients exhibited significantly lower forced vital capacity (FVC) (2,142 mL vs. 2745.6 mL, p < 0.05), higher GAP stages (p < 0.05), and worse quality of life (SGRQ impact scores: 45.2 vs. 27.5, p < 0.05). The identified cutoff values were 2.94 cm2 for RFCSA, 9.19 s for TUG, and 1.08 cm for the RF-Y-axis and body cell mass (BCM) cutoff of 25.4 kg. Kaplan–Meier analysis indicated a higher hazard ratio (HR) for mortality in sarcopenic patients. Specifically, RFCSA sarcopenia patients had a 2.37 times higher risk of events (HR = 2.37, 95% CI: 1.02–5.48, p = 0.045), and TUG sarcopenia presented a 4.89 times higher risk of adverse events (HR = 4.89, 95% CI: 1.43–16.70, p = 0.011). Conclusion Sarcopenia is prevalent in IPF patients and is associated with greater disease severity and reduced quality of life. RFCSA, BCM, and TUG are good predictors of sarcopenia and 12-month mortality, improving the prognostic value of classical diagnostics based on EWGSOP2 criteria. Despite limitations such as a predominantly male sample and cross-sectional design, the findings emphasize the importance of early detection and targeted interventions. Future research should focus on longitudinal studies to better understand sarcopenia progression in IPF and evaluate the efficacy of various therapeutic approaches.